2020
DOI: 10.1093/ajcn/nqaa014
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast before and during early pregnancy and incidence of gestational diabetes mellitus: the Japan Environment and Children’s Study

Abstract: Background There is little evidence linking breakfast skipping to the incidence of gestational diabetes mellitus (GDM). Objectives We aimed to evaluate the prospective association of breakfast consumption with the incidence of GDM. Methods A total of 103,099 pregnancies were registered during study enrollment (January 2011 to March 2014), involving 97,454 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
2
18
1
2
Order By: Relevance
“…A higher proportion of the pregnant women in this study had their lunch or dinner as the largest meal of the day, which is consistent with previous studies that reported a higher proportion of energy consumed at lunch and dinner, i.e., during the later times of the day (45,46). The prevalence of breakfast-skipping in this study was at the upper end as compared to the previously reported prevalence among pregnant women (6-31%) (47)(48)(49). Pregnant women tend to be vulnerable to meal skipping due to factors such as morning sickness, sensitivity to smell, and reduced appetite (50)(51)(52).…”
Section: Discussionsupporting
confidence: 90%
“…A higher proportion of the pregnant women in this study had their lunch or dinner as the largest meal of the day, which is consistent with previous studies that reported a higher proportion of energy consumed at lunch and dinner, i.e., during the later times of the day (45,46). The prevalence of breakfast-skipping in this study was at the upper end as compared to the previously reported prevalence among pregnant women (6-31%) (47)(48)(49). Pregnant women tend to be vulnerable to meal skipping due to factors such as morning sickness, sensitivity to smell, and reduced appetite (50)(51)(52).…”
Section: Discussionsupporting
confidence: 90%
“…Second, the data on skipping breakfast were obtained from the self-reported questionnaires of the participants; thus, misinterpretation of skipping breakfast is inevitable. However, while the percentage of pregnant women skipping breakfast in Japan is 20–30% [ 22 , 23 ], the percentage of women skipping breakfast was almost the same at 25.2% in the present study. Third, the types and amounts of food consumed for breakfast are unknown.…”
Section: Limitationscontrasting
confidence: 51%
“…In addition, blood pressure follows the circadian clock, and disruption of the circadian clock is associated with hypertension [ 20 , 21 ]. However, in Japan, 20–30% of pregnant women miss breakfast [ 22 , 23 ], and irregular dietary intake, such as skipping breakfast, is associated with an increased risk of gestational diabetes and preterm birth [ 22 , 24 ]. However, to the best of our knowledge, no studies have examined the association between skipping breakfast and the development of HDP or HDP subtypes in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Third, GDM incidence was relatively lower in this population compared with that in other populations. We have reported possible explanations elsewhere [29]. Briefly, it may be explained by the lower pre-pregnancy BMI in this population, by different diagnosis criteria used, and by the exclusion of about 800 women with a history or current diagnosis of GDM at the time of study enrollment.…”
Section: Discussionmentioning
confidence: 99%